2018
DOI: 10.1080/09658211.2018.1476551
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bilingual language proficiency on recall accuracy and semantic clustering in free recall output: evidence for shared semantic associations across languages

Abstract: Two experiments investigated how well bilinguals utilise long-standing semantic associations to encode and retrieve semantic clusters in verbal episodic memory. In Experiment 1, Spanish-English bilinguals (N = 128) studied and recalled word and picture sets. Word recall was equivalent in L1 and L2, picture recall was better in L1 than in L2, and the picture superiority effect was stronger in L1 than in L2. Semantic clustering in word and picture recall was equivalent in L1 and L2. In Experiment 2, Spanish-Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
1
5
1
Order By: Relevance
“…We see here that when the lexical items are matched between languages, they are equally difficult or easy to learn. This is in contrast with some previous literature that found that memory tends to be worse in a foreign language 23,46,47 , although these results are not very consistent 48 . This difference in results between memory for known vocabulary and new word learning suggests that either the effect is not very robust, or it does not extend to new vocabulary.…”
Section: Discussioncontrasting
confidence: 99%
“…We see here that when the lexical items are matched between languages, they are equally difficult or easy to learn. This is in contrast with some previous literature that found that memory tends to be worse in a foreign language 23,46,47 , although these results are not very consistent 48 . This difference in results between memory for known vocabulary and new word learning suggests that either the effect is not very robust, or it does not extend to new vocabulary.…”
Section: Discussioncontrasting
confidence: 99%
“…Evidence that long-standing semantic associations are language general comes from studies showing that repetition priming of semantic associations transfers across languages (de la Riva Lopez, Francis, & García, 2012; Francis, Fernandez, & Bjork, 2010; Taylor & Francis, 2017). Also, semantic clustering was equivalent in bilingual L1, bilingual L2, and monolingual recall output (Francis, Taylor, et al, 2018). Evidence that newly learned semantic associations are language general comes from the finding that cued recall and associative recognition of unrelated English word–word paired associates was equivalent for L1 and L2 speakers and equivalent for monolinguals and bilinguals (Francis, Lara, & Strobach, 2018; Papagno & Vallar, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between working memory and bilingualism is discussed explicitly in several studies (e.g., Bonifacci, Giombini, Bellocchi & Contento, 2011;Kaushanskaya, Blumenfeld & Marian, 2011;Orozco, 2020). Some studies (e.g., Antón, Carreiras & Duñabeitia, 2019;Francis et al, 2018;Grundy, 2020) considered the impact of bilingualism on the performance of working memory, whereas other studies (e.g., Morales, Calvo & Bialystok, 2012;Kerrigan et al, 2017;Grundy & Timmer, 2017;Orozco, 2020) explored the advantage of bilingual speakers over monolingual speakers with regard to working memory. So far, previous studies that contrasted bilinguals' and monolinguals' working memory performance have been inconsistent.…”
Section: Literature Review Working Memory and Bilingualismmentioning
confidence: 99%
“…However, other studies reported the opposite (Yoo & Kaushanskaya, 2012;Engel de Abreu, 2011). On the other hand, some studies revealed no apparent difference between monolingual and bilingual speakers in the performance of working memory tasks (Francis et al, 2018;Grundy, 2020;McVeigh, Wylie & Mulhern, 2019). Adesope, Lavin, Thompson and Ungerleider (2010) investigated the effects of bilingualism on cognition in young adults and children.…”
Section: Literature Review Working Memory and Bilingualismmentioning
confidence: 99%